Land Degradation and Population Growth in Sub-Saharan Africa : The Machakos Experience - English, John; Tiffen, Mary; Mortimore, Michael (World Bank, Washington, DC, 2012)
An issue which has generated much concern has been the potential link between low incomes and resource degradation. This report presents the results of a study which investigated this question. Machakos District is a relatively low income and agriculturally marginal district in Kenya. Before World War II the colonial administration was concerned that land degradation was becoming severe under the pressure of population, aggravated by drought. The report analyzes the changes which have taken place in the land resources, agricultural systems, and social structures of the district over the period since 1930. Despite the fact that there was considerable social turbulence in the period prior to independence, the people of the district have managed, building on good market access and periodic government support, to make substantial changes in their government support and agricultural systems and bring about a dramatic increase in the productivity of their land resources.